Will they or won't they eaudiobook A novel. - Wilder, Ava (Books on Tape, 2023)
Onscreen, they’re in love. Offscreen, they can’t stand each other. From the author of How to Fake It in Hollywood comes “a sexy lovers-to-enemies-to-lovers romance that smolders then bursts into flames” (Abby Jimenez, New York Times bestselling author of Part of Your World ). “Wilder takes readers behind the scenes of a television shoot in this fun contemporary romance. . . . Fans of Emily Henry and Christina Lauren should check this out.”— Publishers Weekly A POPSUGAR BEST BOOK OF THE YEAR Lilah Hunter and Shane McCarthy are madly in love—at least, their characters are. As the stars of the hit paranormal TV show Intangible, Lilah and Shane spent years pining for each other onscreen . . . until Lilah ditched the show at the end of season five in hopes of becoming a movie star. With no such luck, she’s back to film the much-hyped ninth and final season, in which Lilah and Shane’s characters will get together at last. But coming back means facing one of the biggest reasons she left: Shane. Ever since their secret behind-the-scenes fling imploded at the end of season one, the two of them have despised each other. Now reunited on set for the first time in years—with the world’s eyes on them and their post-show careers on the line—they’ll have to grit their teeth and play nice. But under pressure to give Intangible ’s fans the happy ending they’ve been waiting for, Lilah and Shane are forced to get closer than ever. And if they’re not careful, they might just get blindsided by one final twist: a real-life happy ending of their own.